2017
DOI: 10.1186/s13223-017-0185-x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic rhinitis: the eligible candidate to mite immunotherapy in the real world

Abstract: As standard drug treatment of allergic rhinitis (AR) is not completely satisfactory, allergen immunotherapy (AIT) represents the only current treatment with the potential to modify the natural history. House dust mite (HDM) allergy is very common. The aim of the current experience was to describe the clinical profile of HDM-allergic patients with AR who received AIT in a real world model, such as allergy clinics. Globally, 239 patients (126 adults and 113 children; 107 females and 132 males; mean age 21 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
4
8
0
Order By: Relevance
“…An Italian real‐world multi‐center observational survey in 17 allergy clinics found a share of children of 25% in the AIT group. However, the authors stated a higher share in pediatric patients was to be expected, which is in line with our data …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…An Italian real‐world multi‐center observational survey in 17 allergy clinics found a share of children of 25% in the AIT group. However, the authors stated a higher share in pediatric patients was to be expected, which is in line with our data …”
Section: Discussionsupporting
confidence: 92%
“…Our findings compare favorably with this observation, as we found a high share of asthma patients at the therapy index date (mite allergoid: 36.9%; control: 41.7%). These results are comparable to the Italian real‐life data that showed that asthma was present in 41% of AIT‐treated patients …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The frequent presence of asthma was also confirmed by a study of 1212 HDMallergic patients (median age: 22 years; 52% women) in France (one of the study countries in the present research) selected for allergen immunotherapy (AIT); 42% suffered from asthma [8]. Likewise, a study of HDMallergic, AIT-eligible patients in Italy (also a study country in the present research) found an asthma prevalence of 41% [9].…”
supporting
confidence: 77%
“… 2 Although AIT has long duration, expensive cost, and sometimes limited efficacy, there is the need to well define the characteristics of ideal eligible candidates for HDM-AIT as recently appointed. 3 On the other hand, AR may frequently be associated with other upper airway disorders, including nonallergic rhinitis (NAR). NAR presents symptoms caused by non-immunoglobulin E (IgE)-mediated pathogenesis.…”
mentioning
confidence: 99%